2002
DOI: 10.1002/path.1136
|View full text |Cite
|
Sign up to set email alerts
|

FK409 inhibits both local and remote organ damage after intestinal ischaemia

Abstract: In addition to localized tissue injury, intestinal ischaemia-reperfusion (I/R) leads to remote organ damage, in particular to the lungs. Given that nitric oxide (NO) can attenuate I/R-induced tissue injury in many situations, this study evaluated the effects of the NO donor, FK409, on leukocyte adhesion in the microcirculation of the intestinal villus and also assessed pulmonary tissue damage after intestinal I/R injury. PVG rats were subjected to 30 min intestinal ischaemia and a sub-group of animals received… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0
3

Year Published

2003
2003
2011
2011

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 29 publications
2
16
0
3
Order By: Relevance
“…It is well known that the serum levels of TNF-␣, IL-1, or IL-6 are elevated after intestinal reperfusion and that these pro-inflammatory cytokine levels reflect animal mortality [22][23][24][25]. The biological properties of TNF-␣ and IL-1 are very similar in that they are primarily released from macrophages during the early phase of an inflammatory response, and they stimulate endothelial cells and macrophages to release IL-6 and IL-8 [26,27].…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that the serum levels of TNF-␣, IL-1, or IL-6 are elevated after intestinal reperfusion and that these pro-inflammatory cytokine levels reflect animal mortality [22][23][24][25]. The biological properties of TNF-␣ and IL-1 are very similar in that they are primarily released from macrophages during the early phase of an inflammatory response, and they stimulate endothelial cells and macrophages to release IL-6 and IL-8 [26,27].…”
Section: Discussionmentioning
confidence: 99%
“…Microscopically, the areas of necroses were associated with total stasis of blood flow. This patchy response is consistent with previous studies [1,17]. Because of this patchy response, the antimesenteric incision for the exposure of the mucosa was made in a relatively viable segment of the ileum which was associated with an area of reflow in order to study the effects of IR injury and PDTC.…”
Section: In Vivo Fluorescence Microscopymentioning
confidence: 53%
“…Collectively, these observations give the appearance of a dense interstitium. 35 Some of these changes can be seen within minutes after reperfusion. Acute lung injury seen in our study is consistent with that described by others, with diffuse, patchy hemorrhage observed grossly, and interstitial and intra-alveolar edema, alveolar hemorrhage, and fi brin microthrombi seen on microscopic examination.…”
Section: Discussionmentioning
confidence: 97%